The Effectiveness of Al-‘Arabiyyah Lil Athfal's Pocket Book in Improving Vocabulary Understanding for Children at TPA Al Muna 3 Samarinda - Rahmita, Maulidia; Masdar, Ihsanuddin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2023)
Nowadays, the use of foreign languages is very necessary, including the Arabic language, because of its role as a support in communicating in the global world. In learning Arabic, one of the most important elements to learn is vocabulary. Learning vocabulary will make it easier for children to learn language skills, including reading skills, speaking skills, listening skills, and writing skills. The purpose of this study was to determine the effectiveness of Al-'Arabiyyah lil Athfal’s Pocket Book in improving vocabulary understanding for children at TPA Al-Muna 03 Samarinda. This research uses a quantitative approach because it is pre-experimental. The design of this research is a one-shot case study. The respondents were 16 students of TPA Al-Muna 03 Samarinda. Based on the results of data analysis, it can be seen in the hypothesis test using the one-sample t test that student learning is characterized by positive results, with the final score calculated by the one-sample t test formula showing that the average learning outcome of the experimental class is 88. = 9, 37 after the final calculation with the one sample t test. Then, referring to the distribution table with dk = 16-1 = 15 and a significance level of 5% obtained, = 2, 131. Because > , the hypothesis is accepted and is rejected. As a result, the pocket book al-'arabiyyah lil athfal can be interpreted as being effective in increasing vocabulary at TPA Al-Muna 03 Samarinda.